Toxin-producing Clostridium perfringens in cooked cereal food in restaurants in Bangladesh (Bangladesh Veterinarian, 2024)
Clostridium perfringens causes food poisoning in humans worldwide and C. perfringens beta toxin is associated with improperly heated or reheated cooked food. A study was undertaken to determine the prevalence of beta toxin-producing C. perfringens in cooked Plain rice, Pulao, and Biryani in different types of restaurants (general, well furnished) of four districts [Dhaka (north and south city corporation area), Cumilla, Narayangonj, Gazipur)] of Bangladesh. A total of 200 food samples were examined for the presence of C. perfringens and its beta toxin. The positive samples were further tested for the CPB gene (236 bp) of beta toxin-producing C. perfringens using PCR assay. Three samples had C. perfringens (1.5%), in food samples of the restaurants in Dhaka South City Corporation (DSCC). Beta toxin-producing C. perfringens was in one sample (0.5%) in a sample of pulao in the same area during the winter. It is suggested that the prevalence of beta toxin-producing C. perfringens was low but, further studies are required in other cities in Bangladesh.Bangl. vet. 2023. Vol. 40, No. 1-2, 8–15